Improvement of emulsification of egg yolk powder: protein modification techniques - Rui Chuang; Mengzhuo Liu; Dekun Meng; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Ahmed M. Rayan; Mohamed Ghamry (Food Science of Animal Products)
As a high nutritional value egg processing product, egg yolk powder has a wide range of applications, However, its emulsification is affected by the processing conditions and is not satisfactory, which limits its wide application in the food industry. Based on this, this paper presents a systematic review of emulsification modification techniques for egg yolk powder, including physical, chemical, and enzyme modification techniques, to improve its emulsification properties and processing adaptability, and to provide a reference for solving such problems. The characteristics of various modification methods were analysed and compared. Future research should focus on optimising the modification process, gaining a deeper understanding of the modification mechanism and developing more mechanisms for the joint application of modification techniques, to maximise the application potential of egg yolk powder and to meet the growing and diversified needs of the food industry.